1997
DOI: 10.1016/s0022-5223(97)70006-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary adenovirus-mediated transfer of immunosuppressive cytokine genes prolongs allograft survival

Abstract: Intracoronary gene transfer of immunosuppressive cytokines to cardiac allografts is efficient and effectively prolongs graft survival. Vectors that would induce long-term expression of such genes may make this approach clinically applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…Local gene transfer of immunomodulatory cytokines, for example, IL-10 has been shown to prevent graft rejection in various transplant models including the cornea. 13,[15][16][17][18] However, the results presented here indicate that local expression of IL-10 is not sufficient to prevent corneal graft rejection in a full mismatched rat transplant model. Liposome-mediated gene transfer in corneal endothelial cells has been suggested as an interesting technology without inducing immune responses against the transfected cells.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Local gene transfer of immunomodulatory cytokines, for example, IL-10 has been shown to prevent graft rejection in various transplant models including the cornea. 13,[15][16][17][18] However, the results presented here indicate that local expression of IL-10 is not sufficient to prevent corneal graft rejection in a full mismatched rat transplant model. Liposome-mediated gene transfer in corneal endothelial cells has been suggested as an interesting technology without inducing immune responses against the transfected cells.…”
Section: Discussionmentioning
confidence: 64%
“…13,14 Gene transfer and gene therapy leading to IL-10 expression in allogeneic transplants may therefore be a promising therapy to impair effective antigen presentation, reduce graft immunogenicity and inhibit inflammation. Indeed, it has been shown that gene transfer of IL-10 led to prolonged graft survival in different transplant models including the cornea, 13,[15][16][17][18] however, in the latter one, the mechanism of graft prolongation is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The lower transcription of IL-4 vs IL-10 was further evidenced in the remarkable and proportional decrease at both mRNA and protein levels. Many investigators have reported the poor correlation in the gene transfer efficiency between a reporter gene and a therapeutic gene, or between two therapeutic genes (15,38). It seems that each gene has its own rate of transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The pathologic characteristic of this mismatch acute rejection model has been described previously (4,15). Briefly, under general anesthesia, median sternotomy was performed on donor rabbits, both superior and inferior venae cavae were ligated, then cardiac arrest was induced by infusion of University of Wisconsin solution (4°C, 20 ml/kg, 120 ml/h) through an aortic cannula (4).…”
Section: Heterotopic Functional Cervical Heart Transplantation Modelmentioning
confidence: 99%
See 1 more Smart Citation